Daddy-Long-Legs - Webster, Jean. (New York : Bantam, 1985)
A seventeen-year-old orphan is sent to a posh northeastern college for women by an anonymous benefactor. All she must do is write to the man she nicknames Daddy-Long-Legs and tell him of her progress.
920